ISLAM DAN TRANSFORMASI SOSIAL DALAM PERSPEKTIF KUNTOWIJOYO - Mulia, Muji (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2018)
Kuntowijoyo is one of the Indonesian Muslim thinkers who are very concerned in the field of social transformation while Islam must uphold the transcendental values ​​of God Almighty. According to Kuntowijoyo, humans always make social changes and the Qur’an must be become a paradigm and thought base. As a consequence of transformational religion, Islam makes its adherents as agents of social in social change. To carry out the social transformation, the next agenda is to look for devices and tools to mobilize social dynamics. In that time, a prophetic social science that has an epistemological basis for the Qur’an is needed. At the same time, the Qur'an must be made into a paradigm of thinking in understanding social reality. Kuntowijoyo believes that with the Qur'anic paradigm that offers theoretical values ​​transformed into social reality, so with the Qur'an, Islam will be able to build civilization. Without being based on the Qur'anic paradigm, according to Kuntowijoyo, social change will lead to misleading change and civilization